2D-QSAR, Docking, Molecular Dynamics Simulations with the MM/GBSA Approaches against Graves' Disease and PTPN22 - Emmanuel Israel Edache; Adamu Uzairu; Paul Andrew Mamza; Gideon Adamu Shallangwa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Graves' disease (GD) is an autoimmune condition that frequently causes hyperthyroidism and thyrotoxicosis. Protein tyrosine phosphatase, non-receptor type 22 (lymphoid) isoform 1 (PTPN22), is a promising therapeutic candidate for treating GD, rheumatoid arthritis, type 1 diabetes, and other autoimmune disorders. In this dataset, 31 molecular compounds and two standard drugs were optimized using the semi-empirical PM7 theory method via MOPAC v22.0.4 to reveal the key influencing factors contributing to their grave's disease inhibition activity and selectivity. Using QSARIN software, the acquired properties/descriptors were used to create a quantitative structural activities relationship (QSAR) model, and the similarities between the observed and predicted pIC50 values were examined. A molecular docking simulation study also uncovers non-covalent interactions between the investigated compounds and the receptors. The observed ligand-protein interactions with GD proteins (PDB ID 2XPG and 4QT5) and PTPN22 (PDB ID 3BRH) were investigated. The pharmacokinetics (ADMET) properties were also investigated. Finally, molecular dynamics (MD) simulation and MM/GBSA studies that demonstrated stable trajectory and molecular properties with a consistent interaction profile were used to validate the stability of the compounds in the complex with PTPN22.